ANALISIS PAJAK RESTORAN TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) KOTA SUNGAI PENUH: AFRIYANTI - AFRIANTI, AFRIANTI (LPPM STIA Nusantara Sakti, 2024)
This research aims to find out how big the influence of restaurant taxes is on increasing local original income in Sungai Penuh City. This type of research uses a quantitative approach. The data collection techniques in this research are observation and document study. The sampling technique used in this research uses saturated sampling by making the entire population the sample, namely the report on the realization of restaurant tax payments in 2018-2022. It can be seen that the restaurant tax does not have a significant influence on increasing original local income in the City of Sungai Penuh. The magnitude of the influence of the restaurant tax on increasing the original local income in the City of Sungai Penuh is 37%. low and the form of the relationship is positive. It is hoped that the Sungai Penuh City government will further increase the potential for regional tax revenues, especially restaurant taxes, because restaurant taxes still have a small influence. As well as exploring other potentials outside the variables studied, in order to increase local original income.